2010
DOI: 10.1038/modpathol.2010.109
|View full text |Cite
|
Sign up to set email alerts
|

Local immune response in the microenvironment of CIN2–3 with and without spontaneous regression

Abstract: Fifteen to thirty percent of cases with histologically confirmed CIN2-3 in cervical biopsies regress spontaneously (ie, show CIN1 or less in the follow-up cervical cone). The balance between immune-reactive cells from the host and high-risk human papillomavirus (hrHPV) genotypes may provide a biological explanation for this phenomenon. We retrospectively studied 55 cases of CIN2-3 in a cervical biopsy with subsequent cervical cone to assess whether hrHPV genotypes (by AMPLICOR and Linear Array tests) CD4, CD8,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 41 publications
(40 reference statements)
3
56
0
2
Order By: Relevance
“…The most common high-risk types are the HPV-16 and HPV-18, respectively, associated with pre-cancers and cancers in various anogenital sites (e.g., cervix, vulva, vagina, and anus) (3)(4)(5)(6). The studies showed that HPV-specific T-cell responses induced by vaccines play an effective role in tumor regression (7)(8)(9)(10). The researchers indicated that therapeutic HPV vaccines have the potential to inhibit the tumor growth by targeting HPV oncoproteins (11).…”
Section: Introductionmentioning
confidence: 99%
“…The most common high-risk types are the HPV-16 and HPV-18, respectively, associated with pre-cancers and cancers in various anogenital sites (e.g., cervix, vulva, vagina, and anus) (3)(4)(5)(6). The studies showed that HPV-specific T-cell responses induced by vaccines play an effective role in tumor regression (7)(8)(9)(10). The researchers indicated that therapeutic HPV vaccines have the potential to inhibit the tumor growth by targeting HPV oncoproteins (11).…”
Section: Introductionmentioning
confidence: 99%
“…8 Adding to the challenge of assessing noncorrelating histopathologic follow-up findings after HSIL Paps, many high-grade lesions spontaneously regress, especially in younger adults. [9][10][11][12][13][14] With the advent of Food and Drug Administration (FDA) -cleared routine Pap and high-risk (hr) human papillomavirus (HPV) DNA cotesting for women 30 and older, 15,16 an increasing number of women with HSIL Pap test results now also have hrHPV DNA test results available to further assess histopathologic follow-up findings and to potentially help inform follow-up management decisions. 17 Nonetheless, reports on the range of expected histopathologic follow-up outcomes for large numbers of patients with HSIL Pap results based on widely used FDA-cleared liquid-based cytology (LBC) and from-the-vial hrHPV DNA testing remain limited.…”
mentioning
confidence: 99%
“…Concerning the predictive value of cell density for the outcome of LSIL, we found that none of the cell types assessed has such a potential, a finding in accordance to previous studies [58]; nevertheless, our results need to be corroborated using a larger sample. There are very few studies addressing the issue of lesion progression in relation to tissue immunity: in one study, regression of HSIL is related to lower numbers of stromal CD138+ plasma cells [59], whereas in another, macrophage density seems to increase in persistent or progressing LSIL in comparison to regressing ones [18]. On the other hand, assessment of systemic immunity has so far yielded controversial results: whereas one study shows that immune responses quantified by ELISPOT assays in peripheral blood do not predict regression of HSIL [60], another shows HPV16 E2-and E6-specific T lymphocyte responses (quantified by interferon-gamma ELISPOT) to correlate with progression or persistence of LSIL [61].…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained in each analysis were processed automatically by the system. CLART ® HPV 2 kit allowed the detection of infection and coinfection of 35 different HPV genotypes, namely 6,11,16,18,26,31,33,35,39,40,42,43,44,45,51,52,53,54,56,58,59,61,62,66,68,70,71,72,73,81,82,83,84, 85 and 89 [24]. Diagnostic sensitivity and specificity of the CLART ® HPV 2 kit amount to 98.2% and 100% respectively, according to the manufacturer.…”
Section: Hpv Genotypingmentioning
confidence: 99%